2022
DOI: 10.1038/s42004-022-00742-z
|View full text |Cite
|
Sign up to set email alerts
|

Defect-induced tuning of polarity-dependent adsorption in hydrophobic–hydrophilic UiO-66

Abstract: Structural defects in metal–organic frameworks can be exploited to tune material properties. In the case of UiO-66 material, they may change its nature from hydrophobic to hydrophilic and therefore affect the mechanism of adsorption of polar and non-polar molecules. In this work, we focused on understanding this mechanism during adsorption of molecules with different dipole moments, using the standard volumetric adsorption measurements, IR spectroscopy, DFT + D calculations, and Monte Carlo calculations. Avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…For each molecule, the defect concentration has only a small impact on the adsorbed loading at low loadings, but at higher loadings, the presence of defects leads to substantial changes in the adsorbed amount. The trend of CO 2 adsorption isotherm from our study agrees with the previous studies of Wu et al and Jajko et al Further discussion of the data for UiO-66 can be found in the SI. The simulated adsorption isotherms of ethane, ethene, CO 2 , and H 2 S for HKUST-1, IRMOF-1, and ZIF-8 are shown in Figures S6–S8.…”
supporting
confidence: 91%
See 2 more Smart Citations
“…For each molecule, the defect concentration has only a small impact on the adsorbed loading at low loadings, but at higher loadings, the presence of defects leads to substantial changes in the adsorbed amount. The trend of CO 2 adsorption isotherm from our study agrees with the previous studies of Wu et al and Jajko et al Further discussion of the data for UiO-66 can be found in the SI. The simulated adsorption isotherms of ethane, ethene, CO 2 , and H 2 S for HKUST-1, IRMOF-1, and ZIF-8 are shown in Figures S6–S8.…”
supporting
confidence: 91%
“…Tan et al reported experimental evidence that COO – and H 2 O are the capping agent in some treatments of UiO-66 . Our capping choice is chemically similar and has also been used in multiple previous studies. ,, …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the presence of defects is of great effect on adsorption properties. In previous studies, we demonstrated the effect of the presence of defects on the adsorption of water, 24 polar and nonpolar molecules, 29 and carbon dioxide capture. 23 Based on the refined force field for toluene adsorption in ideal UiO-66, adsorption isotherms in defective materials were also calculated.…”
Section: T H Imentioning
confidence: 99%
“…The UiO-66 material is known to contain structural defects, the concentration of which can be controlled by the synthesis temperature. Experimental studies (TG, EA, adsorption experiments) made it possible to determine the type of defects so formed. , It was shown that they are vacancies of linkers–bulky fragments, significantly increasing the available void fraction. Therefore, the presence of defects is of great effect on adsorption properties.…”
mentioning
confidence: 99%